2020
DOI: 10.1177/1744806919900717
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic effects of polydatin through the blockade of neuroinflammation in a chronic pain mouse model

Abstract: Background: Chronic pain is frequently comorbid with anxiety disorder, thereby complicating its treatment. Polydatin, a component from the root of Polygonum cuspidatum, has shown neuroprotection in the central nervous system. However, its effects on pain and anxiety processing have been rarely investigated. In this study, mice were injected with complete Freund's adjuvant (CFA) at the hindpaw to induce pain-and anxiety-like behaviors. Results: Treatment with polydatin (25 mg/kg) alleviated the anxiety-like beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…Again, the CFA-injected mouse model is used to induce pain and anxiety-like behaviors synchronously. In accordance, Guan et al (31) administered CFA in the hind paw to produce pain-and anxiety-like behaviors, and 7 days later, they observed the anxiolytic effects of polydatin by suppressing inflammatory cytokines in the amygdala in this model. Corroborating such findings, our previous data are consistent in suggesting the CFA-experimental model for temporomandibular inflammatory nociception for 10 days as generating an anxiolytic-like response (2).…”
Section: Discussionsupporting
confidence: 60%
“…Again, the CFA-injected mouse model is used to induce pain and anxiety-like behaviors synchronously. In accordance, Guan et al (31) administered CFA in the hind paw to produce pain-and anxiety-like behaviors, and 7 days later, they observed the anxiolytic effects of polydatin by suppressing inflammatory cytokines in the amygdala in this model. Corroborating such findings, our previous data are consistent in suggesting the CFA-experimental model for temporomandibular inflammatory nociception for 10 days as generating an anxiolytic-like response (2).…”
Section: Discussionsupporting
confidence: 60%
“…A study has demonstrated that polydatin improves lipopolysaccharide (LPS)-induced acute respiratory distress syndrome (ARDS). In addition, polydatin has mediated Parkin-dependent mitophagy and protects against mitochondria-dependent apoptosis in ARDS [ 209 , 210 ] niae (MP) infection, MP can infect both the upper and lower respiratory tracts, was found to be suppressed by polydatin treatment through inhibition of the NACHT domain-, leucine-rich repeat-, and pyd-containing protein 3 inflammasome (NLRP3) and the nuclear factor-κB pathway after MP infection [ 211 ]. Actually, several in vivo studies have reported an important protective role of polydatin treatment via different mechanisms in ovalbumin-induced bronchial asthma as well as in LPS-induced acute lung injury [ 212 , 213 ].…”
Section: Polydatinmentioning
confidence: 99%
“…Our results showing that exposure to CCI increased TNFα and IL-1β in the amygdala is consistent with these findings. One study showed that suppressing inflammatory cytokines in the amygdala could alleviate the anxiety-like behavior in a chronic pain mouse model (Guan et al, 2020). The administration of IL-1β-neutralizing antibody prevents the spared nerve injury-induced memory deficits and depressive and pain behaviors (Gui et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that excessive neuroinflammation is one of the key mechanisms for generating and sustaining chronic pain (Ji et al, 2014). Accumulating evidence suggests that high levels of neuroinflammation occur in the amygdala (Burke et al, 2013;Guan et al, 2020). Recently, emerging evidence has suggested that the dopaminergic system plays a critical role in regulating motivational and emotional behavior, including mood and pain modulation (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%